Water contamination emergencies : monitoring, understanding and acting - Borchers, Ulrich; Thompson, K. C. 1944- (Special publication (Royal Society of Chemistry (Great Britain)) ;, 2011)
This book is the proceedings of the International Conference on Water Contamination Emergencies: Monitoring, Understanding, Acting held in October 2010. The fourth in a series of conference proceedings this book develops themes from three previous, highly successful Water Contamination conferences in addition to dealing specifically with four new principle themes: monitoring, understanding, acting and lessons learned. With contributions from leading scientists and experts in academia and industry it offers a truly international perspective on our ability to deal with water contamination emergencies. Emphasis is given to prevention, strategy and unusual emergency incident situations relating to drinking water. The book appeals across the board from public health and environmental professionals to companies, agencies, regulators and experts involved in emergency planning and response.